PELAKSANAAN KONSELING CLIENT CENTER DENGAN MEDIA ONLINE DI MADRASAH TSANAWIYAH SWASTA NURUL ISLAM INDRAGIRI HULU - Zatrahadi, M. Fahli; Mudjiran, Mudjiran; Nirwana, Herman; Karneli, Yeni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Someone client center counseling-centered because the counselor and client are in a psychological contact relationship. The purpose of the study was to describe the implementation of client center counseling with online media. The research is qualitative with the following stages: determining questions, collecting informant data, getting data, and reporting. The informants comprised one teacher of counseling and guidance and five students of private MTs Nurul Islam. The results of the research based on Nvivo coding that the client center counseling has a core theme that supports the reception in counseling, client center and direction. The results of coding Nvivo online counseling develop a supporting theme, namely counseling constraints. Based on this, implementing client center counseling with online media can run even though the major obstacle is internet signal and the media used is WhatsApp with the videocall feature. The application of online counseling at MTs Swasta Nurul Islam fosters independence, emotional management, and making the right decisions for the students’ future.